Social context reform : a pedagogy of equity and opportunity - .; Thomas, P. L. (Paul Lee), 1961- (New York : Routledge, 2014)
"Currently, both the status quo of public education and the "No Excuses" Reform policies are identical. The reform offers a popular and compelling narrative based on the meritocracy and rugged individualism myths that are supposed to define American idealism. This volume will refute this ideology by proposing Social Context Reform, a term coined by Paul Thomas which argues for educational change within a larger plan to reform social inequity--such as access to health care, food, higher employment, better wages and job security.Since the accountability era in the early 1980s, policy, public discourse, media coverage, and scholarly works have focused primarily on reforming schools themselves. Here, the evidence that school-only reform does not work is combined with a bold argument to expand the discourse and policy surrounding education reform to include how social, school, and classroom reform must work in unison to achieve goals of democracy, equity, and opportunity both in and through public education.This volume will include a wide variety of essays from leading critical scholars addressing the complex elements of social context reform, all of which address the need to re-conceptualize accountability and to seek equity and opportunity in social and education reform"--
Includes bibliographical references and index.
Keywords: Educational change -- United States; Social change -- United States; EDUCATION / Educational Policy & Reform / General; EDUCATION / Philosophy & Social Aspects; EDUCATION / Leadership